An evaluation of models that estimate droplet size from subsurface oil releases. (February 2021) - Cooper, Cortis; Adams, Eric; Gros, Jonas
Abstract: Droplet size substantially affects the fate of oil released from deep subsea leaks. A baseline dataset of volume-median droplet diameters (d50 ), culled from 250 laboratory observations, is used to validate seven droplet-size models. Four models compare reasonably well, having 95% confidence limits in d50 of ±50%. Simulations with a near-field fate model (TAMOC) reveals that the four best-performing models, with d50 of 1.3–2.2 mm, agree similarly with observed fractionation of petroleum compounds in the water column during June 4–July 15, 2010. Model results suggest that, had a higher dose of dispersant been applied at the wellhead during Deepwater Horizon oil spill (DWH), the d50 would have dropped by an order of magnitude, reducing surfacing C1 –C9 volatiles by 3.5×. Model uncertainty is found to be substantial for DWH-like blowouts treated with chemical dispersants, suggesting the need for further droplet-size model improvement. Highlights: Roughly 250 high-quality lab experiments of oil droplet-size are now available. Comparisons with observations show the best droplet-size models have confidence limits of ±50%. Inaccuracies in predicted oil droplet-size can substantially affect calculated fates. Further improvement of droplet-size models is needed, especially validation at field-scales.